Thick-film Piezoceramic Micro-generators - Kok, Swee Leong; Harris, Nick; White, Neil (Institute of Measurement and Control, UK, 2008)
Wireless sensor networks have recently become a popular area of active research as they offer the possibility for implementation within the our environment for monitoring physical conditions such as pressure, temperature, acceleration, vibration, and chemical substance present around us. The networks of these systems are built up from a large number of single unit sensor nodes. A sensor node is generally small in physical size (typically a few cm3 or smaller) and consist of a sensor, a transceiver, and supporting electronics. They are connected as a wireless network and are sometimes isolated and embedded in structures, which are not easily accessible. The lifespan of the sensor node is critically dependent upon the power source it contains. Instead of using a limited lifespan source, such as battery as the main power source, ambient energy scavenging offers an improved solution for providing power to miniature sensor nodes for an indefinite period of time. There are several possible mechanisms for ambient energy scavenging including solar, acoustic, thermoelectric, and mechanical vibration. As low-level mechanical vibrations are present in many types of environment this is one possible energy source for harvesting. Basically there are three methods for mechanical vibration to electrical energy conversion: electromagnetic, electrostatic, and piezoelectric. With the decrease in power requirements for Very Large Scale Integrated (VLSI) components for sensor nodes (in the range of a few tens to hundreds of microwatts), the application of piezoelectric materials as micro-generators for harvesting energy from ambient vibration is feasible and has advantages over other techniques in terms of their relatively simple fabrication and the capability for integration with other electronic components.